Some Features of the Lithuanian Resistance Phenomenon - Anušauskas, Arvydas (Genocidas ir rezistencija, 2003)
Speaking presently about the post-war resistance, it is already possible to refer to authentic documentation, which allows analysis of the political and ideological features of the resistance. However, one cannot always avoid schematism when analyzing outcomes of the armed resistance and the very phenomenon of the resistance. The peculiarities of the Lithuanian resistance can be of different aspects too: emphasizing the tragedy of the outcomes, duration, mass character, impact on the creative work of the nation, etc.